Metafora Religiusitas dalam Syair Barzanji Karya Abu Ja’far Al Barzanji Telaah Sastra Islam - Titik Wahyuni; Ines A.W Chasanah; Tri Prihatin Hidayatillah (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Through the beauty of its metaphor, poetry has a very strong appeal to the listener and the reader. The existence of poetry is often an important part of the means of communication, especially in preaching. Barzanji's poem is a form of representation of the life of the Prophet Muhammad PBUH which is framed in the form of a very beautiful metaphorical sentence. This study aims to analyze and describe religious values in the form of metaphorical sentences in the poem Barzanji by Abu Ja'far Al-Barzanji which is related to the religious values of the Prophet. The method used in this study is qualitative descriptive with data in the form of word order. The data were analyzed referring to religious values consisting of exemplary values, glory, purity, respect, and compassion. The results of this study show that Barzanji's poems contain religious values that are shaped in metaphors. The analysis of religious values in Barzanji's poems is important as an effort to provide an understanding that the existence of literary works has a very important role in strengthening spiritual identity in the present and the future. Through the study of Islamic literature, it can teach about the importance of strengthening religious teachings as a guide to achieve the true goals of life. This research produces references in maintaining Islamic values in the world of education. The richness of religious values in Barzanji's poems which is directly guided by the behavior of the Prophet can be one of the reasons for the importance of analyzing Islamic literary works.